Peningkatan Keterampilan Motorik Halus Anak Usia 5 – 6 Tahun Melalui Permainan Edukatif Puzzle Di Tk Negeri 01 Kota Bangun Kutai Kartanegara - Heppy Liana; Hasta Rita; Lailatul Hidayah (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
Fine motor skills are an important factor in early childhood development, based on the identification of problems in Kindergarten 01 Kota Bangun, it was found that there were several identified problems, especially in fine motor skills, which were indicated by indicators of skills in using fingers, eye and hand coordination, distinguishing shapes and images, and assembling puzzles that had not been achieved. This study is a classroom action research. This study aims to improve the fine motor skills of children aged 5–6 years through puzzle media in Kindergarten 01 Kota Bangun. The formulation of the problem in this study is how to improve the fine motor skills of children aged 5–6 years through educational puzzle games in Kindergarten 01 Kota Bangun. Fine motor skills involve coordination between the brain, eyes and hands and require appropriate stimulation to develop optimally. The subjects used by the researcher were 10 children, 6 boys and 4 girls. The data collection techniques used in this study were observation, documentation and interviews. After conducting research through educational puzzle games, the results of cycle I were 68% and in cycle II it increased to 96% and had met the criteria for achieving success of 80% of the number of children in Kindergarten 01 Kota Bangun. Based on the results obtained in the study, it was proven that through educational puzzle games, children's fine motor skills could be improved.